Four new species of terrestrial-breeding frogs of the genus Phrynopus (Anura: Terrarana: Craugastoridae) from Río Abiseo National Park, Peru - Rodriguez, Lily O.; Catenazzi, Alessandro (Zootaxa, 2017)
We describe four new species of terrestrial-breeding frogs belonging to the genus Phrynopus from specimens collected on the eastern slopes of the Cordillera Oriental (2800–3850 m) near and within Río Abiseo National Park, Provincia Mariscal Cáceres, Departments of San Martín and La Libertad, northeastern Peru. All four species lack a visible tympanum and inhabit the upper ridges and slopes within or adjacent to the Park. Phrynopus anancites sp. nov. and P. capitalis sp. nov. inhabit the wet montane grasslands on the upper ridges and valleys from 3600 to 3850 m. Phrynopus anancites (SVL = 25.3 mm) has coarsely aerolated skin and olive green coloration and has small vomerine teeth, while P. capitalis (female SVL = 35.6 mm) is characterized by a large head, short limbs, and distinctive dorsal pattern. Phrynopus dumicola sp. nov. (female SVL = 25.3 mm) has a short head and dark colored body with granular skin on the flanks, and is known only from forest patches along the treeline from 3225 to 3550 m, whereas P. personatus sp. nov. (female SVL = 28.2 mm) has a dark facemask and bright yellow groin spots (possibly aposematic), and inhabits a narrow band of continuous tropical montane rain forest from 2890 to 3110 m. We report infection with Batrachochytrium dendrobatidis from one specimen of P. dumicola collected in July of 1988. With the addition of these four new species, Phrynopus now includes 32 nominal species.